The research on the identification, taxonomy, and comparative genomics analysis of nine Bacillus velezensis strains significantly contributes to microbiology, genetics, bioinformatics, and biotechnology - Sousa, Eduarda Guimarães; Campos, Gabriela Munis; Viana, Marcus Vinícius Canário; Gomes, Gabriel Camargos; Rodrigues, Diego Lucas Neres; Aburjaile, Flavia Figueira; Fonseca, Belchiolina Beatriz; de Araújo, Max Roberto Batista; da Costa, Mateus Matiuzzi; Guedon, Eric; Brenig, Bertram; Soares, Siomar; et al. (Frontiers in Microbiology, 2025)
IntroductionNext-generation sequencing (NGS) has played a pivotal role in the advancement of taxonomics, allowing for the accurate identification, differentiation, and reclassification of several bacteria species. Bacillus velezensis is a Gram-positive, facultatively aerobic, spore-forming bacterium known for its antimicrobial and antifungal properties. Strains of this species are highly relevant in agriculture, biotechnology, the food industry, and biomedicine.MethodsIn this study, we characterized the genomes of nine Bacillus strains isolated from soil in the state of Bahia (Brazil) using NGS with Illumina platform. Identification was performed by Average Nucleotide Identity (ANI) and digital DNA-DNA hybridization (dDDH) analyses, which revealed a match between the genomic information of the isolates and B. velezensis NRRL B-41580, with a variation of 89.3% to 91.8% by dDDH in TYGS and 95% to 98.04% by ANI in GTDBtk.Results and discussionTwo strains, BAC144 and BAC1273, exhibited high similarity to B. amyloliquefaciens subsp. plantarum FZB42. However, the latter strain was subsequently reclassified as B. velezensis. The division pattern observed during identification was confirmed in the phylogenomic analysis, where BAC144 and BAC1273 clustered with Bacillus amyloliquefaciens subsp. plantarum, while the other strains clustered with B. velezensis NRRL B-41580, forming a clade with high genetic similarity, with a bootstrap value of 100%. Furthermore, a synteny analysis demonstrated greater conservation among the strains from this study compared to the reference strain, with the formation of distinct collinear groups. The pangenome analysis revealed an open pangenome, highlighting the genetic diversity within the species. Based on this analysis, a functional annotation was performed to compare exclusive gene repertoires across groups, uncovering distinct adaptations and functional profiles. The identification of bacterial strains belonging to this species is of great importance due to their high applicability. The strains identified in this study underscore the need for more robust taxonomic technologies to accurately classify prokaryotes, which are subject to constant evolutionary changes, requiring the reclassification of several species within the genus Bacillus, many of which are heterotypic synonyms of B. velezensis like Bacillus oryzicola, B. amyloliquefaciens subsp. plantarum and Bacillus methylotrophicus.